Evaluation of The Officer’s Behaviour in Public Services of The Nuclear Minerals Technology - Madyaningarum Madyaningarum (BATAN, 2020)
Service behaviour is defined generally as service behaviour that refers to official job descriptions and service scripts and completes core service tasks using standard service procedures. Evaluation of the behaviour of service officers has the opportunity to trigger continuous improvement in service quality to improve organizational performance—primary data from 73 questionnaires, which are the result of customer satisfaction assessment of nuclear mineral technology services. Data analysis used descriptive frequency statistics that provide a typical condition of the diversity of data. The behavioural evaluation results show that service personnel is polite, not selective; all customers have the same position, officers complete services according to the agreed period, officers complete services following service requirements. This research provides evidence that uncertainty in serving customers requires frontline employees to take personal initiative to anticipate customer needs, prevent and eliminate potential obstacles in service delivery, and continuously identify new opportunities to improve service quality.